Odpowiedzi

Najlepsza Odpowiedź!
2010-03-16T20:17:15+01:00
3(x do potęgi 2-2x+3)-2(x do potęgi drugiej -5x-1) dla x=2,
3(x²-2x+3)-2(x²-5x-1)=3x²-6x+9-2x²+10x+2=x²+4x+11
dla x=2 otrzymujemy
2²+4*2+11=4+8+11=23

a(2ab+b)-b(a-2ab+a do potęgi drugiej)dla a=0,1 i b=-10
(2ab+b)-b(a-2ab+a²)=2ab+b-ab+2ab²-a²b=ab+b+2ab²-a²b
dla a=0,1 i b=-10 otrzymujemy
0,1*(-10)-10+2*0,1*(-10)²-(0,1)²*(-10)=
=-1-10+20+0,1=9,1
4 2 4
2010-03-16T20:21:25+01:00
A) 3(2 do potęgi 2-2*2+3)-2(2 do potęgi drugiej -5*2-1)=
3(4+2-4+3)-2(4-10-1)= 12+6-12+9-8+20+2=69
b)0,1(2*0,1*(-10)-10)+10(0,1-2*0,1*-10+0,1 do potęgi drugiej)=
= 0,1( 0,2* (-10) -10)+10(0,1-0,2*-10+0,01)=
= 0,1( -20-10)+10(0,1-2-10+0,01)=
= -2-1+1-20-100+0,1= (-121,9)
1 1 1